Risk of congenital anomalies in children of parents occupationally exposed to low level ionising radiation. Issue 9 (September 1997) - Green, L M; Dodds, L; Miller, A B; Tomkins, D J; Li, J; Escobar, M
Abstract : OBJECTIVES: To evaluate the risk of having a child with a congenital anomaly in relation to occupational exposure to low level ionising radiation in the pre-conception period. METHODS: A case-control study based on the Canadian congenital anomalies registry used record linkage techniques to identify congenital anomalies among male and female workers in Canada's largest electric company. Cases were defined as parents of a child with a congenital anomaly born between April 1979 and December 1986 who had a congenital anomaly diagnosed within the first year of life. Controls were an individually matched sample of parents of a liveborn child without an anomaly. Risk of congenital anomaly was assessed in relation to parental exposure to ionising radiation acquired through work within a nuclear generating station of an electric power company. Exposure was assessed according to employment, whether or not the worker was monitored for radiation exposure, and quantitative estimates of radiation dose. RESULTS: Employment within the electric power industry was not associated with an increased risk of congenital anomalies in the offspring of mothers or fathers. Risk estimates for workers monitored (those who are likely to be exposed to ionising radiation) were 1.75 (95% confidence interval (95% CI) 0.86 to 3.55) for mothers and 0.84 (95% CI 0.68 to 1.05) for fathers. Exposure for fathers before conception, defined cumulatively and for six months before conception, was not associated with increased risk of anomalies in their offspring. There were no significant increases in risk found between type of anomaly and any measure of exposure, although the statistical power in these groups was limited. The study had insufficient numbers to evaluate the effects of ionising radiation in mothers as only three mothers had recorded doses > 0 mSv. CONCLUSIONS: Overall, workers in a nuclear power industry, and specifically those exposed before conception to low levels of ionising radiation, do not appear to be at an increased risk of having a liveborn child with a congenital anomaly.